Exploring youth consumer behavior in the context of mobile short video advertising using an extended stimulus–organization–response model - Tian, Kun; Xuan, Wenxia; Hao, Lijie; Wei, Wenjing; Li, Dongping; Zhu, Lu (Frontiers in Psychology, 2022)
Under the hit of the epidemic, an increasing number of young people exchange and purchase goods by watching and resorting to mobile short video advertisements. Therefore, it is of great significance to explore the influence mechanism of mobile short video advertising on the consumption behavior of young people. This study develops a theoretical framework including fashion, socialization, entertainment, personalization, brand, and psychological needs with consumption behavior using a stimulus-organism-response(SOR)theory. The data from 334 young people using mobile short video advertising revealed that psychological needs exerted significant impacts on consumption behavior, serving as significant mediators of the advertisements and consumer behavior. The attributes of advertising, including fashion, socialization, entertainment, personalization, and branding, significantly promote the psychological satisfaction of young people. In addition, fashion and brand attribute directly impact consumer behavior.